Structure and optical-mechanical properties of the Zr-Y-O coatings deposited by pulse magnetron sputtering on optical glass; IOP Conference Series: Materials Science and Engineering; Vol. 511 : Perspective Materials of Constructional and Medical Purpose - Ivanova A. V.; Dorofeeva T. I.; Kalashnikov M. P. Mark Petrovich; Bozhko I. A. Irina Aleksandrovna; Fedorishcheva M. V. Marina Vladimirovna; Sergeev V. P. Viktor Petrovich; Khristenko Y. F. (2019, 2019)
Title screen